Strength and dimensional stability of phenolic-treated bamboo-laminated panel - A. Rahman, Nor Fadhlia Farhana (2015)
Laminated plybamboo panels were prepared using bamboo (Gigantochloa scortechinii) slivers that have been treated with phenol formaldehyde (PF) resin. The main purpose of the study was to develop a strong and dimensionally stable bamboo laminated panel. The epidermis and inner layer of the bamboo strips were removed and finally dressed using a sliver machine into 2-mm thick slivers. Bamboo slivers were dried to 12% moisture content in a kiln drying set at 40ºC and 60% relative humidity (RH) for a week. Phenol formaldehyde resin of medium molecular weight (MMwPF), MW1500, was used to pre-treat the bamboo slivers. Two methods were used; vacuum impregnation and soaking. A process for the treatment of bamboo slivers comprising impregnating with MMwPF resin were subjected into a vacuum pressure at 42 cmHg for 15 min, followed by applying the external pressure at 2.5 kg/cm2 for 30, 60 or 90 min. Meanwhile, in the soaking treatment, the slivers were submerged in MMwPF resin for 30, 60 or 90 min. The phenolic-treated bamboo slivers were pre-cured at 60ºC for 6 h. Following this, the phenolic-treated bamboo slivers were assembled perpendicularly into 3-layered plybamboo panel and hot pressed at 140 ± 5ºC and pressure 40 kg/cm2 for 15 min.All the boards were trimmed and cut into test specimens and then conditioned at 20 ± 3ºC and RH 65 ± 3% for a week prior to testing. The weight percent gain (WPG), contact angle, buffering capacity and thermogravimetric analysis (TGA) of phenolic-treated bamboo slivers were determined. The bonding shear strength of 3-layered plybamboo was also evaluated according to British Standard European Norm BS EN 314. The results showed that vacuum-impregnated bamboo slivers had significantly higher WPG compared to the soaked slivers. An examination on the bamboo sliver surfaces demonstrated that phenolic treatment had increased the contact angle of the bamboo surfaces, suggesting a relatively lower wettability. Compared to the control, such reduction is an advantage as it prevents over penetration of adhesive into the cells due to high porosity of the surface. Buffering capacity study revealed that phenolic-treated bamboo slivers have a greater resistance toward alkaline and was more sensitive towards acid. The thermal stability of phenolic-treated bamboo sliver was found to be significantly higher than the untreated. The results also showed that irrespective of the treatment methods used, modulus of rupture (MOR) and impact strength were significantly affected (at p ≤ 0.01) by the treatment method, whereas treatment duration does not indicate any significant effect. A notable improvement in the dimensional stability of treated sample was shown by the reduction of water absorption (WA), thickness swelling (TS) and linear expansion (LE). Treatment with phenolic resin was found to markedly increase the anti-swelling efficiency (ASE) (at p ≤ 0.05) of the phenolic-treated plybamboo suggesting a reduction in irreversible swelling. Conversions of phenolic-treated bamboo slivers into 3- and 5-ply bamboo boards appear to have different effects. The 3-ply phenolic-treated plybamboo had greater flexural strength properties (MOR and MOE) and shear bond strength compared to the 5-ply. In the 5-ply phenolic-treated plybamboo however, demonstrated a greater compressive strength. It was also recognized that the 3-ply phenolic-treated plybamboo at [0°/45°/0°] significantly generate higher MOR. Nevertheless, the 3- and 5-ply phenolic-treated plybamboo had comparable bonding shear properties when arranged at [0°/0°/0°] and [0°/0°/0°/0°/0°], respectively. In addition, the angle configuration at [45°/90°/45°] and [45°/90°/45°/90°/45°] in the 3- and 5-ply phenolic-treated plybamboo, respectively, gave relatively lower MOR values. The overall results revealed that vacuum impregnation was effective compared to soaking. Based on this study, vacuum impregnation for 90 min resulted in significant improvements in the physical and mechanical properties of phenolic-treated plybamboo. Also, this study showed that the angle configuration of the bamboo slivers had greater influence over the mechanical properties of the plybamboo. The WA, TS and LE were found to be much lower in the 3-ply plybamboo indicating a much stable board.